Chromium complexes bearing disubstituted organophosphate ligands and their use in ethylene polymerization. Issue 1 (12th December 2019) - Tavtorkin, Alexander N.; Korchagina, Sof'ya A.; Komarov, Pavel D.; Vinogradov, Alexey A.; Churakov, Andrei V.; Nifant'ev, Ilya E.; Minyaev, Mikhail E.
Abstract : Novel chromium complexes with disubstituted phosphate anions exhibit dinuclear cores, terminal and bridging organophosphate coordination modes, and hydrogen bonding in their crystal structures. As precatalysts, the complexes are capable of polymerizing ethylene. Abstract : The crystal structures of three unusual chromium organophosphate complexes have been determined, namely, bis(μ‐butyl 2, 6‐di‐ tert ‐butyl‐4‐methylphenyl hydrogen phosphato‐κ O :κ O ′)di‐μ‐hydroxido‐bis[(butyl 2, 6‐di‐ tert ‐butyl‐4‐methylphenyl hydrogen phosphato‐κ O )(butyl 2, 6‐di‐ tert ‐butyl‐4‐methylphenyl phosphato‐κ O )chromium]( Cr — Cr ) heptane disolvate or Cr2 (μ2 ‐OH)2 [μ2 ‐PO2 (OBu)(O‐2, 6‐ t Bu2 ‐4‐MeC6 H2 )‐κ O :κ O ′]2 [PO2 (OBu)(O‐2, 6‐ t Bu2 ‐4‐MeC6 H2 )‐κ O ]2 [HOPO(OBu)(O‐2, 6‐ t Bu2 ‐4‐MeC6 H2 )‐κ O ]2 ·2C7 H16, [Cr2 (C19 H32 O4 P)4 (C19 H33 O4 P)2 (OH)2 ]·2C7 H16, denoted (1 )·2(heptane), [μ‐bis(2, 6‐diisopropylphenyl) phosphato‐1κ O :2κ O ′]bis[bis(2, 6‐diisopropylphenyl) phosphato]‐1κ O, 2κ O ‐chlorido‐2κ Cl ‐triethanol‐1κ 2 O, 2κ O ‐di‐μ‐ethanolato‐1κ 2 O :2κ 2 O ‐dichromium( Cr — Cr ) ethanol monosolvate or Cr2 (μ2 ‐OEt)2 [μ2 ‐PO2 (O‐2, 6‐ i Pr2 ‐C6 H3 )2 ‐κ O :κ O ′][PO2 (O‐2, 6‐ i Pr2 ‐C6 H3 )2 ‐κ O ]2 Cl(EtOH)3 ·EtOH, [Cr2 (C2 H5 O)2 (C24 H34 O4 P)3 Cl(C2 H6 O)3 ]·C2 H6 O, denoted (2 )·EtOH, and di‐μ‐ethanolato‐1κ 2 O :2κ 2 O ‐bis[bis(2, 6‐diisopropylphenyl) hydrogen phosphato‐κ O ][bis(2, 6‐diisopropylphenyl) phosphato‐κ O ]chlorido(ethanol‐κ O )chromium( Cr — Cr ) benzene disolvate or Cr2 (μ2 ‐OEt)2 [PO2 (O‐2, 6‐ i Pr2 ‐C6 H3 )2 ‐κ O ]2 [HOPO(O‐2, 6‐ i Pr2 ‐C6 H3 )2 ‐κ O ]2 Cl2 (EtOH)2 ·2C6 H6, [Cr2 (C2 H5 O)2 (C24 H34 O4 P)2 (C24 H35 O4 P)2 Cl2 (C2 H6 O)2 ]·2C6 H6, denoted (3 )·2C6 H6 . Complexes (1 )–(3 ) have been synthesized by an exchange reaction between the in‐situ ‐generated corresponding lithium or potassium disubstituted phosphates with CrCl3 (H2 O)6 in ethanol. The subsequent crystallization of (1 ) from heptane, (2 ) from ethanol and (3 ) from an ethanol/benzene mixture allowed us to obtain crystals of (1 )·2(heptane), (2 )·EtOH and (3 )·2C6 H6, whose structures have the monoclinic P 21, orthorhombic P 21 21 21 and triclinic P space groups, respectively. All three complexes have binuclear cores with a single Cr—Cr bond, i.e. Cr2 O6 P2 in (1 ), Cr2 PO4 in (2 ) and Cr2 O2 in (3 ), where the Cr atoms are in distorted octahedral environments, formally having 16 ē per Cr atom. The complexes have bridging ligands μ2 ‐OH in (1 ) or μ2 ‐OEt in (2 ) and (3 ). The organophosphate ligands demonstrate terminal κ O coordination modes in (1 )–(3 ) and bridging μ2 ‐κ O :κ O ′ coordination modes in (1 ) and (2 ). All the complexes exhibit hydrogen bonding: two intramolecular Ophos …H—Ophos interactions in (1 ) and (3 ) form two H[PO2 (O R )2 ]2 associates; two intramolecular Cl…H—OEt hydrogen bonds additionally stabilize the Cr2 O2 core in (3 ); two intramolecular Ophos …H—OEt interactions and two O…H—O intermolecular hydrogen bonds with a noncoordinating ethanol molecule are observed in (2 )·EtOH. The presence of both basic ligands (OH − or OEt − ) and acidic [H(phosphate)2 ] − associates at the same metal centres in (1 ) and (3 ) is rather unusual. Complexes may serve as precatalysts for ethylene polymerization under mild conditions, providing polyethylene with a small amount of short‐chain branching. The formation of a small amount of α‐olefins has been detected in this reaction.